PENGELOLAAN PERIKANAN TUNA (Thunnus sp) DENGAN PENDEKATAN EKOSISTEM (STUDI KASUS DOMAIN SOSIAL EKONOMI DI PPI UJONG BAROH ACEH BARAT PROVINSI ACEH - Mohamad Gazali; Edwarsyah Edwarsyah; Nilam Shantica; Salmah Salmah (Universitas Teuku Umar, 2017)
We focused on socio-economic aspect to West of Aceh’s Fishermen. The research aims to analyze the socio-economical domain of Tuna (Thunnus sp) in fisheries management based ecosystem approach to fisheries management (Case study at PPI Ujong Baroh). The study was conducted from January – March 2016 that is located at PPI Ujong Baroh West of Aceh. The sampling method is purposive sampling through depth interview and questionnaire. Data analysis method is flag modeling techniques with the approach Multi-Criteria Analysis (MCA). The result shown that the assessment to indicate the fisheries conflict and the utilization of indigenous knowledge were categorized good condition because there is local institution (lembaga laot) that managed and arranged regulations of fisheries management in West of Aceh. This local institution was lead by Panglima Laot. Moreover, the assesment of stakeholder participation was categorized moderate condition. The participation of stakeholder has not ran yet effectively in Tuna fisheries management at West of Aceh. For economical domain shown that income of fisheries household and saving ratio were categorized bad conditions. Most fishermen possess debt to require life necessity before fishing. In other side, Tuna fisheries depend on season and mostly wives also don’t have sufficient knowledge to increase their income through fish processing. Moreover, the asset ownership has shown “medium” condition. According to fishermen, their productive asset stil likely to constant if we compared in the previous year.